Formation of professional and communicative foreign language competence in future technology engineers by means of authentic texts - Tamara Medzhidovna Cheucheva (Вестник Майкопского государственного технологического университета, 2023)
The article is devoted to the use of authentic texts in teaching a foreign language in a technical university. The relevance of the research is associated with globalization and integration processes taking place in modern society, with the rapid development of science and advanced information technologies. In the context of expanding international contacts and establishing relations with foreign partners, training of highly qualified engineers requires the improvement of the methodology of professionally oriented foreign language teaching. The aim of the research is to justify the appropriateness of using non-adapted authentic texts as a necessary condition for professional and communicative foreign language competence formation of future specialists. Methods of observation, comparison, analysis have been used in the research. The author has analyzed various scientific approaches to the use of texts in the process of professional foreign language teaching; arguments regarding the inefficiency of using constructed and simplified authentic texts have been presented, advantages of working with non-adapted original sources at the first stage of the educational process have been noted. In the article the author shares his observations on increasing the motivation of students to master the language of a future profession, introduces personal experience in delivering texts and methods of working with them at various stages of education using the example of the Bachelor's course “Land Management and Cadastres”. The paper notes the results achieved by using non-adapted authentic texts to the educational process: overcoming the psychological language barrier, increasing linguistic and professional motivation, activating educational activities, and optimizing the learning process. The author comes to the conclusion that well-chosen and correctly used texts contribute to successful implementation of the goals of professionally-oriented teaching of a foreign language at a technical university.